Focal Scalp Hair Heterochromia in an Infant - Kumar, Pramod (Sultan Qaboos Univ Med J, 2017)
Hair heterochromia involves the presence of two different non-artificially induced colours of hair in the same individual which can be due to either iron deficiency anaemia, genetic mutations or mosaicism. We report a six-month old male infant who presented to the Department of Dermatology, Saham Hospital, Saham, Oman, in 2013 with focal scalp hair heterochromia without any detectable underlying abnormalities. The area of heterochromia was still noticeable at a one-year follow-up.